مولد المسيح بين الأناجيل والقرآن الكريم - دراسة مقارنة - - قااسمم, إحسان; بوحنيك, خديجة; اللبددي, رقية (جامعة الوادي university of eloued, 2019)
إن شخصية المسيح عيسى بن مريم عليه السلام اختلف حولها الكثير من الآ ا رء، من ميلاده إلى نهايته، إلى أن ميلاده كان أكبر معجزة من الله خلقه من غير أب عندما ألقى كلمته إلى مريم العذ ا رء، ولما بشرت من الله بأنها ستحبل ثم تلد ابنا يكلم الناس في المهد، وسيكون وجيها في الدنيا والآخرة ومن المقربين، وكل هذا ذكر في القرآن أما الإنجيل اختلف واتفق في بعض النقاط وموضوع بحثنا المقارنة بينهما، ونسأل الله أن يوفقنا. Research Summary The personality of Jesus Christ, the son of Mary, peace be upon him, differed widely from his birth to the end, until his birth was the greatest miracle of God he created without a father when he delivered his word to the Virgin Mary. When she preached to God that she would conceive and give birth to a son, and will be valid in the world and the Hereafter and close, and all this mentioned in the Koran, the Bible differed and agreed on some points and the subject of our research comparing them, and ask God to help us.
ليسانس